On Some Motifs in Poetics - Mermigki, Dimitra (Epistēmēs Metron Logos, 2020)
This text is dedicated to the Emeritus Professor of Analytical Philosophy and Poet, Aristophanes (Αris) Koutougos. From his prolific poetry (published, or under publication), emerges a dialectic of a characteristic poetic idiom, his own "Aristophanean-poetry". Its main element is the delimitation of the poetic shape in the breadth of the surface of artistic creation within philosophical depth in general. Ηis poetic discourse super-vises time reflections on the structural rivalries of its declarative propositions which, eventually, reshape the complexity and purify the uncontrolled outbursts or "sharp remainders" of the dramatized (comic-tragic) event. A.K. approaches poetry and philosophy by opening a new discussion about the idea of an aesthetic dialectic with painting, music and song, mostly in natural everyday language as philosophically influenced.